FIRST LANGUAGE ACQUISITION, THE PROCESSES AND DEVELOPMENT - Sarwanti, Sri . (Majalah Transformatika, 2010)
This article attempts to find out the processes and development of first language Acquisition. The processes are started from the first day children are born. Because of the existence  of  a  device  called Language Acquisition Device (LAD) the children are able to undergo several stages before they eventually  arrive  to  a  position  which enables them to master the first language. The stages are reflexive crying and vegetative sounds, cooing and laughter, vocal Play, reduplicated babbling, non-reduplicated babbling  and  expressive jargon. Keywords :first language, LAD, processes, first words, first meaning, fis  phenomenon